Forecasting and Replenishment in the Aerospace After-Sales Market - The Case of Pattonair Ltd - Bilkhu, Amardeep (2010)
The After Sales market has intermittent and lumpy demand which makes forecasting and Inventory Management extremely difficult. Common methods lose their applicability. In order to meet customer demand, organisations result in holding large amounts of inventory. There are increased pressures to reduce cost of operations and operate as a collaborated supply chain network. The move towards Servitisation by Manufacturers requires extra resources and increased management. Initiatives such as Collaborative, Planning, Forecasting and Replenishment and Information sharing can improve relationships between organisations and can lead to increased efficiency. Pattonair Ltd supply Rolls Royce with parts for the Civil Aftermarket (Aerospace) business and this research compares their practices against theoretical models, concepts and frameworks that are recommended for the After Sales Supply Chain.